2010
DOI: 10.1063/1.3303988
|View full text |Cite
|
Sign up to set email alerts
|

B diffusion in implanted Ni2Si and NiSi layers

Abstract: B diffusion in implanted Ni 2 Si and NiSi layers has been studied using secondary ion mass spectrometry, and compared to B redistribution profiles obtained after the reaction of a Ni layer on a B-implanted Si͑001͒ substrate, in same annealing conditions ͑400-550°C͒. B diffusion appears faster in Ni 2 Si than in NiSi. The B solubility limit is larger than 10 21 atom cm −3 in Ni 2 Si, while it is ϳ3 ϫ 10 19 atom cm −3 in NiSi. The solubility limit found in NiSi is in agreement with the plateau observed in B prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…It diffuses only at 550°C, when the concentration becomes homogeneous in NiSi. Additional profiles (not shown here) show that the B concentration is already homogeneous after annealing the same sample at 500°C for only 1h [11]. This result is different fromwhat was observed for the diffusion of B that was implanted in preformed NiSi, where diffusion was observed at a temperature as low as 400°C.…”
Section: Diffusion In Materials -Dimat 2011contrasting
confidence: 67%
“…It diffuses only at 550°C, when the concentration becomes homogeneous in NiSi. Additional profiles (not shown here) show that the B concentration is already homogeneous after annealing the same sample at 500°C for only 1h [11]. This result is different fromwhat was observed for the diffusion of B that was implanted in preformed NiSi, where diffusion was observed at a temperature as low as 400°C.…”
Section: Diffusion In Materials -Dimat 2011contrasting
confidence: 67%
“…The diffusion of atoms may vary significantly from one phase to another since the atomic diffusion mechanisms can differ from phase to phase. For example, the diffusion coefficients of As 35 and B 36,37 were shown to exhibit large variations in Ni 2 Si and NiSi in grains, as well as in GBs. In addition, stress effects on atomic diffusion 30,38-41 were not taken into account in our simulations.…”
Section: E Comparison With Experimental Resultsmentioning
confidence: 99%
“…However a recent study 29 has shown that the solubility of B in Ni 2 Si is larger than 10 21 at/ cm 3 ͑i.e., about 2 at. Two peaks appear below the Ni film and a large amount of boron is observed both in NiSi 2 and NiSi.…”
Section: Resultsmentioning
confidence: 93%